2006
DOI: 10.1002/chem.200600575
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Reactions of [60]Fullerene Involving Tertiary Amines and Insight into the Reaction Mechanisms

Abstract: Thermal reactions of [60]fullerene with amino acid ester hydrochlorides and triethylamine in o-dichlorobenzene at reflux afforded pyrrolidinofullerene derivatives containing the CH(3)CH moiety and originating from triethylamine through an unusual C-N bond cleavage. Detailed investigation of these thermal reactions resulted in the discovery of unprecedented reactions between C(60) and tertiary amines and of reactions of C(60) with tertiary amines and aldehydes, giving cyclopentafullerene derivatives with high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…[6,7] In contrast, a more plausible mechanism for the thermal reaction between C 60 and TEA was regarded to be a 1,3-dipolar cycloaddition process, involving acetaldehyde and diethylamine intermediates (Figure 8, a). [10] To confirm this, we try to identify the existence of the intermediates with GC-MS spectroscopy. Indeed, characteristic mass/ion peaks of acetaldehyde at m/z 44.0 (Figure 8, b) and diethylamine at m/z 73.1 (Figure 8, c) were detected, unambiguously confirming the 1,3-dipolar cycloaddition mechanism.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[6,7] In contrast, a more plausible mechanism for the thermal reaction between C 60 and TEA was regarded to be a 1,3-dipolar cycloaddition process, involving acetaldehyde and diethylamine intermediates (Figure 8, a). [10] To confirm this, we try to identify the existence of the intermediates with GC-MS spectroscopy. Indeed, characteristic mass/ion peaks of acetaldehyde at m/z 44.0 (Figure 8, b) and diethylamine at m/z 73.1 (Figure 8, c) were detected, unambiguously confirming the 1,3-dipolar cycloaddition mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…[9] Recently, Wang group investigated the reaction of C 60 and TEA under thermal conditions, and proposed the formation of the pentane cycloaddition derivative (Figure 1, D). [10] So far, there are no Xray crystallographic reports for the structure of fullerene derivatives from the reaction between C 60 and TEA, nor the mechanism has been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…28 Wang et al has also reported on the unusual C-N bond cleavage when C 60 is reacted with triethylamine. 36 The formation of numerous reaction products would potentially result in the formation of sources of free radicals or charge carrier traps as observed by Duan et al when analyzing interactions of amine functionalized fullerenes and polymers with an OPV active layer. 10 …”
mentioning
confidence: 93%
“…Interestingly, compound 15 has recently been obtained in 39 % yield by heating C 60 with sarcosine ethyl ester hydrochloride and Et 3 N in o-dichlorobenzene (o-DCB) at 220°C under dark and aerobic conditions through a mechanism involving radical species. [17] Although the mechanism for the formation of compound 15 lacking the thiol moiety from 14 is not clear, other related cases, probably involving a radical mechanism, have been reported in the literature. [18] It is worth mentioning that although compound 15 was not the goal in this reaction (C 60 , 12, and 13), it does provide a facile access to 2-methyl-substituted pyrrolidinofullerenes which would otherwise require the presence of acetaldehyde as a reagent in Prato's protocol.…”
Section: Resultsmentioning
confidence: 97%